Pengaruh Aplikasi Sistem Edukasi Masa Nifas (SEMASA) Terhadap Perilaku Perawatan Ibu Nifas di Rumah Sakit Humana Prima Bandung: The Influence of The Application of the Education System in Postpartum Period (Semasa) on the Care Behavior of Public Women at Humana Prima Hospital Bandung - Herawati, Yanti; Mahwati, Yeni; Sutisna, Ma’mun; Sastramihardja, Herri S; Nurlatifah, Teni; Lestari, Mia Dwi (LPPM STIKES Guna Bangsa, 2025)
Approximately 50% of maternal deaths occur within the first 24 hours after delivery. Cesarean section (CS) delivery can lead to more complications compared to vaginal delivery. At Humana Prima Hospital, the incidence of CS deliveries was 1035 in 2021, 1192 in 2022, and 1426 in 2023. Providing education during the postpartum period is important for increasing maternal knowledge, attitudes, and behaviors. An innovative educational medium, such as the SEMASA application, can be an instrumental in this regard. This study aimed to analyze the influence of using the SEMASA application on maternal knowledge, attitudes, and behaviors in postpartum care. This quantitative study employed a quasi-experimental with a nonequivalent posttest-only control group approach. The research was conducted on 84 postpartum mothers at Humana Prima Hospital in 2023, using purposive sampling to select 42 respondents who used the SEMASA application and 42 respondents who received information through leaflets. Data were analyzed using the Mann-Whitney test. The results revealed significant differences in knowledge, attitudes, and behaviors between the intervention and control groups. In the intervention group, 36 respondents (85.7%) demonstrated good knowledge, compared to 22 respondents (52.4%) in the control group (p<0.05); 36 respondents (85.7%) in the intervention group had a positive attitude, compared to 34 respondents (81.0%) in the control group (p<0.05); 38 respondents (90.5%) in the intervention group exhibited compliant behavior, compared to 26 respondents (61.9%) in the control group (p<0.05). The study concluded that the SEMASA application effectively improves the knowledge, attitudes, and behaviors of postpartum women in their postpartum care.